From habitats to hashtags: examining online discussions about invasive species - Canavan, Susan; Pipek, Pavel; Canavan, Kim; Jarić, Ivan; Healy, Kevin; Lieurance, Deah; Pattison, Zarah; Pyšek, Petr; Stevenson, Emily; Novoa, Ana (Ecology and society, 2025)
Public awareness is critical for societal support for conservation efforts, including management of biological invasions. However, traditional methods for assessing public awareness are limited, and its role as a key factor in alien species invasions remains largely unknown. The rise of participatory web and social media platforms, such as Twitter (rebranded as X), has provided opportunities to gain insight into societal perceptions through user-generated content. In this study, we assessed public discourse about invasive species on social media by analyzing over 500,000 tweets containing the term “invasive species” posted between 2006 and 2021. Our aim was to identify the most frequently mentioned taxa and habitats, prevailing topics, and subject matters that generated high engagement in discussions on biological invasions. We found that mammals, specifically domesticated and urban pests, were the most frequently mentioned, while aquatic habitats and those interfacing with aquatic habitats dominated the top 15 mentioned habitat types. Additionally, the use of location-based hashtags, such as the Great Lakes and Florida, suggests that people tend to be more engaged with invasive species issues in specific areas. We also observed that a relatively small subset of users contributed a disproportionately large share of retweeted content, highlighting the influence of a few key accounts. This study shows the potential of digital data for identifying prominent taxa, habitats, regions, and influential voices in invasive species discussions. Such information can help refine communication strategies, tailor policy interventions, and foster more effective public engagement in efforts to manage and mitigate the impacts of biological invasions.